Preparation and evaluation of herbal shampoo - E, Lakshmi Poojitha; K.M, Dilli Prasad; P, Mani; P, Geethika; Shaik, Khaja Nawaz; P, Saisireesha (International Journal of Indigenous Herbs and Drugs, 2024)
Aim and Objective: The aim of this presents formulation and evaluation herbal shampoo and to assess its physiochemical function that emphasis on safety, efficacy, eliminating harmful ingredient, and substitute with safe natural ingredients. Material and Methods: The formulation of shampoo using the extracts of Hibiscus, Ritha, Alovera, methi, amla, flax seeds, curry leaves and neem leaves different proportions. Evaluation of organoleptic, physicochemical, and performance tests in terms of wetting time test, pH, solid contents, surface tension, dirt dispersion, foam Stability, cleaning action and Viscosity was performed. Results: The created cleanser was clear and good appealing. It demonstrated good foam stability, detergency, good cleansing, small bubble size, low surface strain, and execution of good conditioning. Conclusion: The physicochemical evaluation of the formulated shampoo showed ideal results. However, to improve its quality, product performance, and safety, further development was required.